Entrepreneurial Marketing and Marketing Performance in Gen Z Entrepreneurs: Exploring the Mediating Pathways to Entrepreneurial Resilience - Hasanah, Yulia Nur; Anggraeni, Oki; Suwali, Suwali; Kusnaman, Djeimy; Hasibuan, Reza Rahmadi; Efendi, Bahtiar (Journal of Ecohumanism, 2025)
This study examines how Generation Z in Indonesia performs in marketing and how factors such as entrepreneurial mindset, social support, self-efficacy, and entrepreneurial marketing influence their resilience. A quantitative survey was conducted in 2024 on 6.1 million Generation Z members, with a sample of 400 respondents selected using the Slovin formula (5% margin of error). Results reveal that entrepreneurial marketing positively impacts self-efficacy, social support, entrepreneurial mindset, and resilience, though the effect on self-efficacy is not statistically significant. Entrepreneurial resilience significantly influences marketing performance, highlighting the importance of entrepreneurial attitudes and resilience in achieving marketing success.